Age and gender differences in job opportunities - Stephan Humpert (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
There is only a few literature on age specific occupational segregation. In this descriptive paper, I focus on job opportunities for newly hired older male and female workers. It is an enriched replication study of Hutchens (ILRR,1988), who showed that firms employ older workers, but hire them less. I use a rich dataset for West Germany with information for almost thirty years, the regional file of the IAB Employment Sample (IABS-R04). By drawing segregation curves and calculating different measures, such as Dissimilarity Index and Hutchens Square Root Segregation Index, I find clear evidence that age related segregation exists. While newly hired workers in the age groups of 18 to 34 and 35 to 54 are quiet similar distributed in terms of the indices, the oldest age group of 55 years and older, and especially older women, are more segregated. Differences for older male and female workers over time, may be explained by changes in labor and retirement policies.
Keywords: J23; J24; J21; J14; J16; 330; Labor Demand; Age Segregation; Older Workers; Gender; Arbeitsnachfrage; Ältere Arbeitskräfte; Weibliche Arbeitskräfte; Arbeitsmarktdiskriminierung; Altersdiskriminierung; Geschlechterdiskriminierung; Schätzung; Deutschland